Fruit maturation as a parameter for selection of sweet orange cultivars in Brazil - Cavalcante, Italo H. L.; Martins, Antonio B. G. [UNESP]; Stuchi, Eduardo S.; Campos, Milton C. C. (Wfl Publ, 2009)
The study was carried out to evaluate the fruit maturation of 18 sweet orange cultivars in Bebedouro County, São Paulo State, Brazil. A randomized blocks experimental design was adopted with 18 treatments and four repetitions and each treatment represented an orange cultivar. Soluble solids:titratable acidity ratio, technological index and fruit weight were evaluated trough a regression analysis in each cultivar and group, which were determined by cluster analysis. There were differences among cultivars and groups studied in relation to fruit maturation. Orange cultivars Joao Nunes and Hamlin were the earliest, followed by Kawatta, Mayorca, Rubi and Westin; Pineapple and Tarocco A and Oliverlands, Cadenera and Homosassa, respectively. Torregrosa, Jaffa, Biondo, Finike, Sanguinea, Moro and Early Oblong are later than the other cultivars studied.
Keywords: Citrus; sweet orange; harvest time